Prediction of significant hyperbilirubinemia by estimating cord blood bilirubin in neonates with ABO incompatibility - Singh, Ruchika; Jain, Hemant (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal hyperbilirubinemia is a common condition that may occur in 60-70 % of term babies and the most common pathological cause leading to hyperbilirubinemia is ABO incompatibility. ABO incompatible newborns are reported to be at greater risk of significant hyperbilirubinemia and are associated with significant morbidity like development of kernicterus. So early intervention, at proper time, is mandatory to prevent this sequel. Methods: A prospective study included 240 term new-borns with gestational age of >37 weeks and birth weight >2.5 kg born to ‘O’ blood group mothers. Soon after delivery, cord blood was sent for blood group, total bilirubin and direct coombs test. All enrolled new-borns were assessed clinically daily till day 5th for appearance of hyperbilirubinemia using Kramer method. The data was analysed using descriptive analysis, ROC curve in SPSS version 14. Results: Among two hundred forty ABO incompatible newborns, 40 (17%) had developed hyperbilirubinemia and among them most common blood group associated was B+ve (75%). Association between cord bilirubin content and maximum serum bilirubin content among newborn who developed hyperbilirubinemia was found to be significant (P value <0.01). As per ROC curve analysis, cord blood total bilirubin cut off value of 1.79mg/dl had sensitivity (82.5%), specificity (55.5 %), PPV (27.04%) and NPV (94.06). Conclusions: Cord blood total bilirubin levels ≥1.79mg/dl has a good predictive ability for prediction of significant hyperbilirubinemia among ABO incompatible new-born. DCT is neither specific nor sensitive screening tool for development of Neonatal hyperbilirubinemia in ABO incompatibility.